DIALOGUE OF THE QUR’AN AND SCIENCE: - Zuhdi, M. Nurdin (Hunafa: Jurnal Studia Islamika, 2018)
The aim of the study is to investigate the forms of integration-interconnection of Qur’anc verses and health sciences at Faculty of Health Sciences of Universitas ‘Aisyiyah Yogyakarta. The study also reveals and analyzes the implementation of learning strategy used in the integration-interconnection application of Qur’anic verses and health sciences at University of ‘Aisyiyah Yogyakarta as well as its relevance with campus philosophy as a professional and Qur’anic campus. The study used mixed method by combining 2 methods at the same time (quantitative and qualitative). The approach used in the study was science integration-interconnection approach offered by M. Amin Abdullah. Based on the analysis of the study, it can be concluded that there are 2 forms of integration-interconnection of Qur’anic verses and health sciences at Faculty of Health Sciences, University of ‘Aisyiyah Yogyakarta, namely: Formal integration and Non-Formal Integration. Formal integration is learning process which has been set in university’s learning curriculum as a set of subjects to take each semester. Formal integration consists of 3 forms, namely (1) integration in learning system; (2) integration in students’ thesis; and (3) integration in lecturers’ research in which the lecturers at FIKES must relate or integrate the research with Qur’anic verses. Meanwhile, Non-formal integration is Qur’anic learning outside the subjects or curriculum set by the university. Non-formal learning can be found in additional lessons outside learning subjects. There are 6 forms of non-formal integration, namely Reading Qur’an (BAQ), Islamic Basic Study Orientation (OSDI), Character Management Program (PROPEMKA), Objective Structured Competency in Islamic-values Examination (OSCIE), Baitul Arqam Purna (BAP) and Tahfizhul Qur’an Program (PTQ).